NUTRITIONAL EVALUATION AND FUNCTIONAL PROPERTIES OF Cassia alata FLOWER (FUDMA JOURNAL OF SCIENCES, 2021)
Medicinal plant is a part of plant or the whole plant that possesses healing properties. Itâ€™s of utmost importance in many areas of life. Cassia alata belongs to this class of plants. The present study was carried out to evaluate the mineral elements, proximate, vitamins, phytochemical compositions and infra-red spectra of the flower of Cassia alata plant. The analyses were carried out using standard analytical techniques. The proximate analysis (%) showed that the flower contained ash (7.060Â±0.082), moisture (8.489 Â±0.151), crude fat (12.319 Â± 0.292), crude fibre (16.055 Â±0.756), protein (10.447Â±0.06) and carbohydrate (45.630Â± 0.120). Elemental analysis (ppm) showed the presence of zinc (0.719 Â±0.006), copper (0.071 Â±0.002), nickel (0.0064 Â±0.001) manganese (0.059Â±0.001) and iron (0.061 Â±0.002) in moderate quantity with magnesium (26.577 Â±0.005) and calcium (37.302 Â± 0.020) while phosphorus (106.400 Â± 0.001) was found in large amount. The result from the vitamin analysis (mg/g) revealed vitamin C to be the most abundant vitamin with (37.853Â±0.039mg/g) while the composition of vitamin B1 was (0.244Â±0.002mg/g) and vitamin B2 (0.473Â±0.0009mg/g). Phytochemicals (mg/g) were detected; phenols (14.319Â±0.064), saponins (14.692Â±0.653), flavonoids (13.940Â±0.017) and tannins (1.247Â±0.050). Also, Infra-red characterization of the flower part of the plant indicated some functional properties which are of medicinal benefits to man and animals. This study proposes that the flower of Cassia alata  can serve as good source of nutrients and with potentials as therapeutics
Keywords: Cassia alata, Infra red characterization, therapeutic, medicinal plant, nutrients